OK. Hold on tight. Here we go.
Remember ... the "solution" is the number that 'g' must be
in order to make the equation a true statement.
The original equation: You said that -2 = g - 9
Now, let's add 9 to each side: 7 = g .
f^-1(x) = sq.rt 5(x - 10)/5, sq.rt 5(x - 10)/5 is the inverse of y = 5x^2 +10
Step-by-step explanation:
interchanging the variables
x = 5y^2 + 10
5y^2 +10 = x
5y^2 = x - 10
dividing by 5
5y^2/5 = x/5 + -10/5
y^2 = x/5 + - 10/5
y^2 = x/5 - 2
y = 5 (x-10) 0/5 (sq.rt)
g(5x^2 + 10) = 5x/5
g(5x^2 + 10) = x
f^-1(x) = sq.rt 5(x - 10)/5, sq.rt 5(x - 10)/5 is the inverse of y = 5x^2 +10
Answer:
x = 14
JHK = 21
Step-by-step explanation:
The angles are vertical angles and vertical angles are equal
3x-21 = x+7
Subtract x from each side
3x-x -21 = x+7-x
2x-21 = 7
Add 21 to each side
2x-21+21 = 7+21
2x = 28
Divide by 2
2x/2 =28/2
x = 14
JHK = 3x-21 = 3(14) -21 = 42-21 = 21
Answer:
no Y dose not vary directly with X
aka (A)
Step-by-step explanation: